Identification parameters of material model and large deformation analysis of inflated air-spring shell made of rubber-textile cord composite - Nam, Tran Huu (Vietnam Journal of Mechanics, 2005)
In the paper an orthotropic hyperelastic constitutive model is presented which can be applied to numerical simulation for the response of biological soft tissue and of the nonlinear anisotropic hyperelastic material of the cylindrical air-spring shell used in vibroisolation of driver's seat. The parameters of strain energy function of the proposed constitutive model are fitted to the experimental results by the nonlinear least squares method. The deformation of the inflated cylindrical air-spring shell is calculated by solving the system of five first-order ordinary differential equations with the material constitutive law and proper boundary conditions. Numerical results of principal stretches and deformed profiles of the inflated cylindrical air-spring shell obtained by numerical deformation analysis are compared with experimental ones.